“ECT should never stop”: Exploring the experiences and recommendations of ECT clinical directors and anesthetists about ECT during the COVID-19 pandemic - Branjerdporn, Grace; Sarma, Shanthi; McCosker, Laura; Dong, Vanessa; Martin, Donel; Loo, Colleen (Frontiers in Psychiatry, 2022)
Electroconvulsive therapy (ECT) is an effective treatment option for severe, treatment-resistant, and life-threating psychiatric illness. The COVID-19 pandemic has significantly disrupted ECT services. Services across North America, Europe, and Australia have reported decreased ECT delivery, and changes in the ways ECT is delivered. This study aimed to identify the impacts of COVID-19 on ECT services globally by exploring clinicians’ experiences about ECT during the pandemic, and their recommendations for reducing the negative impacts of the pandemic. Data were collected using an electronic, cross-sectional survey, which included elicitation of free-text responses. The survey was open from March to November 2021. Clinical directors in ECT services, their delegates, and anaesthetists were invited to participate. This paper reports the qualitative analysis of responses provided. Fifty-two participants provided qualitative response/s; 74.5% were clinical directors or their delegates, and 25.5% were anaesthetists. Greater than one-third of participants were from Australia/New Zealand, and there was also representation from North America, Europe, and the UK. Participants’ responses were detailed, averaging 43 words. Three themes were identified: (1) Service provision, about the importance of ECT services continuing during the pandemic, (2) Preparedness, through guidelines and environmental design, and (3) Personal protection, about strategies to increase staff safety. This is the first multi-site, international study to document the experiences and recommendations of ECT clinical directors and anaesthetists about the effect of COVID-19 on ECT practice. The findings inform evidence-based practice, and ensure people with major psychiatric illnesses continue to receive ECT during the pandemic.